Isoniazid resistance profile in rifampicin resistant Mycobacterium tuberculosis - Shareef, Naomee; Saleh, Ahmed Abu; Ibne Sattar, Abu Naser; Anwar, Shaheda (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Background: Multidrug-resistant tuberculosis (MDR-TB) is a global public health problem. Rifampicin (RIF) resistance has been used as a surrogate marker for MDR-TB but isoniazid (INH) resistance within RIF resistance cases is little known. This study aimed to determine the proportion of INH resistance among RIF-resistant MTB. Methods: In this cross-sectional study, from March 2021 to February 2022, 53 RIF-resistant MTB isolates in sputum samples detected by Xpert-MTB RIF assay were enrolled. All samples were tested for mutation in katG (codon 315) and inhA promoter (-5, -8, -15 and -16) genes to detect INH resistance by real-time PCR. Statistical analysis was done using IBM SPSS (version 26). Results: Out of 53 RIF-resistant samples, 15.1% were sensitive to INH, and the rest had concomitant resistance to INH. The proportion of newly diagnosed and previously treated cases was nearly equal, and most of the previously treated cases (92.9%) received treatment regularly. INH-resistant cases were mostly previously treated (55.5%), whereas sensitive cases were mostly newly diagnosed (62.5%). KatG was found to be the prominent mutation, with or without in combination with inhA mutation. Conclusion: A considerable number of RIF-resistant isolates did not show concomitant resistance to INH. Most of the INH-resistant isolates were associated with katG mutation. Evaluation of INH resistance before using high-dose INH will help to avoid dose-dependent toxicity in MDR-TB patients. Bangabandhu Sheikh Mujib Medical University Journal 2023;16(3): 160-166